An evaluation of the South African marine recreational fisheries permit system - Du Preez, Aidan Matthew (Rhodes University, 2026)
Recreational fishing is a popular activity worldwide with millions of fishers harvesting billions of fish annually. With technological advancements and a growing global participation rate, increasing pressure has been placed on fisheries resources. To promote sustainability, the way in which humans interact with these resources requires careful management. However, funding these management strategies is not simple, particularly in Low- and Middle-Income Countries (LMICs). In recreational fisheries, a common source of income for management stems from user-pay funding systems. The use of recreational fishing licenses or permits (referred to as permits in this thesis) is an effective cost-recovery tool to aid in management of these fisheries, while also providing information on the trends in numbers of fishers, information about characteristics of those fishing, and lists of participants for scientific study and communication. However, the efficacy of these user-pay systems is seldom evaluated. South Africa makes use of a permit system for cost recovery of the management of marine-based recreational fisheries. While anecdotal information has suggested that the efficiency of this system is questionable, there is no information to understand the role that it plays in the management of South Africa’s marine recreational fisheries. The aim of this thesis is to evaluate the South African marine recreational fishing permit system by examining and analysing sales trends, the utilisation of the funds generated and the permit preferences of recreational anglers. This information will then be used to develop best practice guidelines for the system. A longitudinal review of the recreational fishing permit sales dataset and government documents revealed the long-term sales trends, income, and associated management activities. Between 2002 to 2019, a total of 5 085 834 marine recreational permits pertaining to the recreational fishery were sold equating to an income of ZAR 767 094 511. Permits with an annual validity were far more popular than permits with a temporary validity and comprised 84.4% percent of total sales contributing ZAR 635 230 700 (94.2% of total) in revenue to the Marine Living Resource Fund. The marine recreational angling permit was the most frequently purchased permit type with a total of 2 899 151 permits sold (mean = 170 538 per annum). Assuming compliance has remained stable and using permit sales as a proxy for participation, participation in marine recreational fisheries is increasing. Furthermore, there is no clear evidence of the funds from recreational fishing permits being used specifically to support recreational fisheries management, enforcement or angling development. After a review of the government’s annual reports on expenditure by the Marine Living Resources Fund, it was established that despite the revenue generated, very little attention is given to the management of recreational fisheries in South Africa. Preferences on aspects of the recreational permits were elicited from existing and former permit holders using a Discrete Choice Experiment (DCE). The DCE was developed by making use of a pilot study that made use of open-ended questions to discern the main themes. These themes were then developed into attributes and levels for the DCE. Results indicated that respondents (n = 166) were highly responsive to aspects of the permit concerning the price (p < 0.001), the physical format of the permit (p < 0.001), the designation of fishing areas (p < 0.001), and the level of law enforcement present within the fishery (p < 0.001). Generally, respondents preferred a lower priced permit, no new fisheries management zones, and increased law enforcement levels. Amending policy to prioritize the use of the funds from recreational fisheries for their management is considered to be an important step to improving overall recreational fisheries governance. Improving the current permit system to reflect preferences of anglers would most likely reduce permit non-compliance and enhance the income received from marine recreational fishers. If mandated for use in the recreational fisheries sector, these additional funds are thought to be crucial in providing aid for management if to engage stakeholders, launch education programmes, conduct research in protected areas, understand participation and effort, and increase public awareness in order to bolster compliance and enhance participation within the fishery.
Keywords: Fish and game licenses (http://id.loc.gov/authorities/subjects/sh85048614); Fishing--South Africa (http://id.loc.gov/authorities/subjects/sh85048830); Discrete choice experiment